THE INFLUENCE OF STUDENTS' EMOTIONAL INTELLIGENCE ON LEARNING OUTCOMES OF THE ECONOMIC LEARNING EVALUATION COURSE AT UNIVERSITAS PANCASAKTI BEKASI - Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2021)
This research aims to reveal the influence of students' emotional intelligence (X) on learning outcomes in the Economic Learning Evaluation course (Y). The research method used is the regression method. The sampling technique uses random sampling. The research sample consisted of 122 students. The results of the research instrument trial showed that the reliability of the learning outcomes instrument for the Economic Learning Evaluation course was 0.912, and emotional intelligence was 0.762. Data analysis uses simple regression analysis. The research results reveal: (1) Linear Regression Equation. Obtained linear equation Y = -43.321 + 0.624X (2) Students' emotional intelligence has a positive effect on learning outcomes in the Economics Learning Evaluation course. (3) Testing the significance of the regression line equation, the F hit and p-value are smaller than 0.05 or Ho is rejected. Thus, students' emotional intelligence influences learning outcomes in the Economic Learning Evaluation course. (4) Testing the significance of the correlation coefficient, the correlation coefficient (rxy) = 0.612 and Fhit (Fchange) = 3,196.836, with a p-value smaller than 0.05. This means Ho is rejected. Thus, the correlation coefficient X and Y is meaningful or significant. Meanwhile, the coefficient of determination R Square = 0.664, which means that 66.4% of the variation in learning outcome variables in the economics learning evaluation course.